2021
DOI: 10.5435/jaaosglobal-d-21-00153
|View full text |Cite
|
Sign up to set email alerts
|

Gap Year Research Fellowship Opportunities for Medical Students Interested in Orthopaedic Surgery

Abstract: Introduction: Orthopaedic surgery is becoming an increasingly competitive specialty. The purpose of this study was to identify existing orthopaedic research fellowships in the United States and to determine important characteristics including the number of positions offered by each program and the average number of publications from completing the program. Methods: An online search was performed to identify year-long orthopaedic research fellowship programs available for me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The academic setting also provides advantages such as resident assistance on research projects or the presence of research fellows to carry the project forward while attendings focus on clinical obligations. Clark et al published a study on the impact of a research fellow and found that the average number of publications gained from completion of a research year was 10.8 [ 19 ]. Every publication that a research fellow successfully brings to print is overseen by an attending surgeon and many of the programs outlined in that study accept >1 fellow, thus exponentially increasing productivity.…”
Section: Discussionmentioning
confidence: 99%
“…The academic setting also provides advantages such as resident assistance on research projects or the presence of research fellows to carry the project forward while attendings focus on clinical obligations. Clark et al published a study on the impact of a research fellow and found that the average number of publications gained from completion of a research year was 10.8 [ 19 ]. Every publication that a research fellow successfully brings to print is overseen by an attending surgeon and many of the programs outlined in that study accept >1 fellow, thus exponentially increasing productivity.…”
Section: Discussionmentioning
confidence: 99%
“…The mean numbers of oral presentations given during 1 year by plastic surgery research fellows and otolaryngology research fellows are 5.4 and 3.68, respectively 21,22 . In addition, on average, research fellows publish anywhere between 5.25 and 10.8 manuscripts, depending on the surgical subspecialty, which would improve one's chances of presenting more frequently 21–23 . However, access to research fellowship opportunities is inequitable.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In addition, on average, research fellows publish anywhere between 5.25 and 10.8 manuscripts, depending on the surgical subspecialty, which would improve one's chances of presenting more frequently. [21][22][23] However, access to research fellowship opportunities is inequitable. First, as of 2021, only 5 funded plastic surgery research fellowships can be found through Google search.…”
Section: |mentioning
confidence: 99%
“…Research fellowships are 1 to 2-year programs that permit medical students or recent graduates to conduct research, present at conferences, and build connections. As of 2020, there were at least 30 orthopaedic research fellowship programs in the United States 10 .…”
mentioning
confidence: 99%